Unconstrained trade: The impact of EU cage bans on exports of poultry-keeping equipment - Shon M. Ferguson (Research Institute of Industrial Economics (IFN), 2021)
This study evaluates the impact of conventional cage bans for laying hens in the EU on exports of poultry-keeping equipment. Using detailed data on international trade in poultry-keeping equipment combined with an event study regression approach yields several new findings. The results suggest that the cage bans were associated with an increase in intra-EU trade, and also an increase in exports of poultry equipment from EU member states to non-EU countries where conventional cages are still permitted. The results suggest that some banned cages were likely exported to countries outside the EU to be used in egg production.
Keywords: F14; F15; Q17; 330; International trade; Policy leakage; Animal welfare